Running Critical Power and W´: Influence of the Environment, Timing and Time Trial Order - Ruiz-Alias, Santiago A.; Ñancupil-Andrade, Alberto A.; Pérez-Castilla, Alejandro; García-Pinillos, Felipe (International Journal of Sports Medicine, 2023)
This study aimed to determine the influence of the testing environment (track vs. treadmill), time trial order (long-short vs. short-long), and timing (within-session vs. between-sessions) on the critical power (CP) and work over CP (W´), using the power metric in runners. Fifteen highly trained athletes performed three test sessions composed of two time trials of 9- and 3-min, separated by a 30-min rest period. One session was performed on a track, and two sessions on a treadmill, alternating the order of the time trials. The CP and W´ values determined on the track were significantly greater and lower than on the treadmill, respectively (p<0.001; CP≥89 W; W´≥3.7 kJ). Their degree of agreement was low (SEE CP>5%; W´>10%) and therefore was not interchangeable. There were no performance differences in the timing of the time trials (p=0.320). Lastly, performing the 9-min trial first resulted in a greater power output compared to when executed last (p<0.001; 4.9 W), although this resulted in similar CP and W´ values (Bias<5 and 10%, respectively). In conclusion, it is feasible to test CP and W´ in a single testing session, irrespective of the time trial order, although not interchangeably between track and treadmill.
Keywords: running; critical power; endurance performance; training